Embryohistiogenesis of Vascular Tufts of Glomeruli: a Possible Hypothesis (Iranian Journal of Kidney Diseases, 2017)
Introduction. Embryogenesis of the kidney glomeruli, especially its vascular component, has not been well documented. Glomeruli capillary tuft is surrounded and enveloped by visceral epithelial cells, which is a unique portal system that connects afferent with efferent arteriole without interaction with venular circulation. We hypothesized that the portal system embryologically has developed by extension of the intima of afferent arteriole into the stroma of glomerulus. We also hypothesized that juxtaglomeruli apparatus was developed from remnants of smooth muscle cells of the media of afferent arteriole at the anastomosing site with the Bowman capsule entrance. Materials and Methods. We studied 5 human fetal kidneys by hematoxylin-eosin, periodic acid-Schiff, and immunoperoxidase staining techniques. Results. Hematoxylin-eosin staining of fetal kidney showed presence of erythrocytes in early vesicle form of glomeruli that was confirmed by immunohistochemical staining with CD31, smooth muscle actin, and CD34 markers. These stains showed extension of extraglomerular arterioles to the glomeruli. Periodic acid-Schiff staining showed also the continuity of the basement membrane in extraglomeruli and internal glomerular vascular tufts. Conclusions. This study shows that there is a relationship between the metanephric blast cells and major vessel critical for angiogenesis. When afferent arteriole come in contact with the immature glomeruli, its intima migrates into the glomerular tuft to form intraglomerular capillary system, while its smooth muscle remains at the entrance orifice and develops juxtaglomerular apparatus cells.